Replication Data for: Fungal endophyte association with Brachiaria grasses and its influence on plant water status, total non-structural carbohydrates and biomass production under drought stress - Odokonyero, Kennedy; Acuña, Tina Botwright; Cardoso Arango, Juan Andrés; Jiménez Serna, Juan de la Cruz; Rao, Idupulapati M. (International Center for Tropical Agriculture, 2016)
The purpose of the data was to gain an understanding of the effect of fungal endophyte on responses of selected Brachiaria cultivars under well-watered and drought conditions. The study was to answer the question as to whether symbiotic association of Brachiaria grasses with fungal endophyte (Acremonium implicatum synonym Sarocladium implicatum) improves plant growth and tolerance to drought stress. This was approached by measuring: • Plant water status, determining as leaf relative water contents (RWC) • Leaf dry matter contents (DMC) • Total non-structural carbohydrate (NSC) contents • Biomass The subject areas of the study involved plant-microbe interactions, plant physiology/biochemistry and plant ecology